Social perspective of domestic wastewater management in Entikong Lama district - Ardhi Ristiawan; Purwono Purwono; Annida Unnatiq Ulya (Sustinere: Journal of Environment and Sustainability, 2019)
Entikong Lama is a densely populated residential area and the center of economic activity located on the riverbank. However, there was poor management of municipal wastewater that influences water quality of the river. Moreover, the river water is used by society for drinking, cooking, bathing, washing and toileting. Hence, municipal wastewater management is needed to prevent river from polluted municipal wastewater. This research is a social analysis to investigate social perspectives on wastewater management planning. This analysis is imperative to find out the social response and willingness of the society towards municipal wastewater management. The social survey was carried out using the interview and questionnaire method. This research found that about 93% of the household already had water closets (WC) and 83% already had septic tanks. The problem that occurs is that the septic tank has never been sucked up because there is no desludging service. This is due to the fact that there are no Fecal Sludge Treatment Plant (FSTP) facilities in the Entikong Lama. Later, communal Wastewater Treatment Plant (WWTP) planning program was offered to the society. About 72% of the household agreed to the communal WWTP program and the rest refused or abstained. Even though it reached high positive response from the society, there were some considerations of the communal WWTP program: the location of the communal WWTP, the clarity of those who manage the wastewater plant and the amount of fees charged to the society.